Improving barrier properties of HDPE using PVA as clay modifier - Carrera, María Celeste (2013)
In this work it was prepared nanocomposites of high density polyethylene (HDPE) with different loads of modified organoclay with polyvinylalcohol (PVA). Modified organoclay was obtained by in situ polymerization of vinyl acetate with an organoclay and the nanocomposites were prepared by melt blending. The structure and morphology of nanocomposites were studied by XRD, SEM and TEM. The heat stability was measured by TGA and DSC. The barrier properties were evaluated by testing of cyclohexane pervaporation and the surface properties were obtained by determination from the contact angle using three solvents at ambient atmosphere. TEM results showed the different types of nanocomposite structures that were obtained with clay layers in the polymer matrix depending on the load of clay incorporated into the polymer matrix. The permeation experiments confirmed that the barrier properties evaluated by cyclohexane pervaporation were remarkably improved and increased in the thermal resistance for HDPE/ organoclay modified with PVA materials compared with pristine HDPE. Results from all studies showed that the addition of modified organoclay has changed the macroscopic properties of nanocomposites, as compared to that pure HDPE. This can be attributed to the different interaction of PVA with HDPE/filler.